Healthy Living for Elders: Keep Track of Your Blood Pressure - Leigh Ann Martin (EDIS)
Every time you take your blood pressure at home, or have it checked by a health professional write down the date and time, the blood pressure measurement, where it was taken (home, doctor’s office, etc.), and any comments from you or the health professional (i.e. medications you are taking or recently stopped taking, how you feel, and the arm where the pressure was taken). This is document FCS 8601-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.